MENGOPTIMALKAN POTENSI SAMPAH ORGANIK UNTUK MENDORONG PERTANIAN BERKELANJUTAN PADA REVIEW SISTEMATIS - Nurani, Maria Puri (Fakultas Pertanian, 2023)
Organic waste management plays a crucial role in supporting sustainable agriculture by recycling valuable resources and reducing environmental impacts. This systematic literature review explores the implementation of organic waste management strategies, including composting, vermicomposting, fermentation, and eco-friendly technologies, in developed countries such as Germany, the Netherlands, and Sweden. The review also highlights the challenges and opportunities in each country, considering technological limitations, social and cultural aspects, as well as policy and regulations. Moreover, it analyzes the implications for sustainable agriculture and provides recommendations for further research. The findings underscore the importance of integrating organic waste management into agricultural practices to enhance soil fertility, reduce greenhouse gas emissions, and promote sustainable farming systems globally.